PENGEMBANGAN E- MODUL BERBASIS FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPAS KELAS V SDN 3 SENDANGREJO - Yunita Zumrotul Muriya; Novialita Angga Wiratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the development process and evaluate the validity, practicality, and effectiveness of a flipbook-based e-module for the IPAS subject in Grade V at SDN 3 Sendangrejo. The research is a development study using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The data collection instruments used include validation sheets by material experts, media experts, and language experts, response questionnaires from teachers and students, as well as pretest and posttest items. Validation results indicate that the e-module is valid with percentages of 98% from the language expert (very valid), 85% from the material expert (valid), and 96% from the media expert (very valid). Practicality tests show a 100% score from students and 98% from teachers, indicating the module is highly practical. The effectiveness test shows a score of 79%, classifying the module as effective in improving learning outcomes. Therefore, the developed flipbook-based e-module is suitable to be used as a valid, practical, and effective learning medium.